Estruturas sedimentares e tectônica sinsedimentar da Formação Araripina, Bacia do Araripe, Nordeste do Brasil - Andrade, André Santiago Martins de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The Araripe Basin is the most extensive interior basin in Northeast of Brazil and presents a complex evolution of its stratigraphic framework related to tectonics that originated the South Atlantic Ocean. The Araripina Formation is part of the post-rift sequence of this basin and it is dated from middle Albian. The unit is composed predominantly of rhythmites with local evidences of synsedimentary deformation such as pseudonodules, injectites and convoluted folds. These deformations are related either to seismic activity (seismites) or to compaction caused by overload which is inherent to the depositional system. Facies and facies association suggest continental paleoenvironment. The sedimentation occurred in distal-fan flat environment, ephemeral lakes and river channels and tectonic lakes. The stratigraphic succession is limited at the base by a lithological unconformity with the basement (or Romualdo Formation) and by erosional unconformity (locally angular unconformity) with Exu Formation at the top. The paleocurrents pattern of Araripina Formation suggests deposition towards east and source-areas at west. Therefore, the paleocurrents pattern towards west shown by Exu Formation indicates a polarized change in sedimentation. This change is product of epirogenetic uplift of the basin which was more intensive at the east portion and rearranged all the Brazilian northeastern continental paleodrainage. The action of syn and post tectonics in Araripina Formation is incisive and it is attributed to reactivations of basement structures during Albian. These reactivations are related mainly to the opening of Equatorial Atlantic Ocean and originated both synsedimentary deformations (syn tectonics) and posterior faults and tilted structures (post tectonics). The occurrence of fractures and faults ... (Complete abstract electronic access below)

A Bacia do Araripe é a mais extensa bacia interior do Nordeste do Brasil. Apresenta complexa evolução tectono-estratigráfica relacionada aos regimes de esforços que originaram o Oceano Atlântico Sul. A Formação Araripina faz parte da sequência pós-rifte desta bacia, tem idade mesoalbiana e é composta predominantemente por ritmitos com evidências localizadas de deformação penecontemporânea, como pseudonódulos, injectitos e dobras convolutas. Essas deformações estão relacionadas ora à atividade sísmica (sismitos), ora à compactação por sobrecarga oriunda de processos inerentes ao sistema deposicional. As fácies e associação de fácies da Formação Araripina sugerem paleoambiente deposicional continental. A sedimentação se deu em planícies distais de leques aluviais, canais de rios e lagos efêmeros e lagos tectônicos. A sucessão como todo está limitada na base por discordância litológica com o embasamento (ou com a Formação Romualdo) e no topo por discordância erosiva (localmente angular) com a Formação Exu. O padrão de paleocorrentes da Formação Araripina sugere mergulho deposicional para leste e áreas-fonte a oeste. Desta forma, as paleocorrentes para oeste da Formação Exu sugerem mudança polarizada da sedimentação, resultado de basculamento da bacia com soerguimento mais intenso da porção leste, reconfigurando a paleodrenagem continental. A ação de tectônica formadora e modificadora na Formação Araripina é incisiva e é atribuída às reativações de estruturas do embasamento durante o Albiano. Essas reativações estão relacionadas, principalmente, à abertura do Oceano Atlântico Equatorial e originaram tanto deformações sinsedimentares (tectônica formadora) como falhas e estruturas basculadas posteriores (tectônica modificadora). A ocorrência de fraturamentos ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Sedimentação e depósitos; Paleocorrentes; Rochas - Deformação; Brasil, Nordeste; Araripe, Rio, Bacia